Meningkatkan Minat Belajar Siswa Dengan Penerapan Model Make A Match Di Sekolah Dasar - Fisul, Fisul (Science and Education Journal (SICEDU), 2024)
.This research aims to improve students' listening skills through the Make A Match model for class II students at SD Negeri 007 Pendalian for the 2023/2024 academic year. The type of research used is Classroom Action Research. This research consisted of 2 cycles and each cycle was held in 2 meetings. Data analysis techniques are carried out using qualitative and quantitative descriptions. This research was carried out in 2 cycles, each cycle lasting 2 meetings. The research results showed that students' listening skills improved after the action. The results of the research show that using the Make A Match model can increase the interest of class II students at SD Negeri 007 Pendalian. This is shown by an increase in the number of students who reach the minimum completeness criteria (KKM) and an increase in the average class and classical scores. The average value of students' interest in learning before the action was 57.1% with a sufficient category, then in cycle I they got an average of 67.9% also in the sufficient category and in cycle II they got a class average of 85.7% with very good category.